PENGARUH MASA JABATAN, GENDER, UMUR DAN PENDIDIKAN CEO TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022) - Megawati, Megawati; Yesi, Basri Mutia; Hariadi, Yasni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
This research aims to analyze: (1) the effect of CEO tenure on firm value, (2) theeffect of CEO gender on firm value, (3) the effect of CEO age on firm value, (4)the effect of CEO education on firm value. This research also use, company age,company size and dividend payout ratio as control variables.The population inthis research are banking companies listed on the Indonesian Stock Exchange(BEI) in 2019-2022. In this research, the sample selection technique usedpurposive sampling to obtain a sample of 34 companies. This research usessecondary data obtained from company annual reports. This research usesmultiple linear regression data analysis with analysis, namely (SPSS). The resultsobtained from this research prove that the CEO's tenure and age influence thevalue of the company, and the CEO's gender and education have a negativeinfluence on the value of the company. Keywords: CEO Tenur; CEO Gender; CEO Age; CEO Education and Firm Value